2010
DOI: 10.1186/1471-2121-11-102
|View full text |Cite
|
Sign up to set email alerts
|

Lack of α8 integrin leads to morphological changes in renal mesangial cells, but not in vascular smooth muscle cells

Abstract: BackgroundExtracellular matrix receptors of the integrin family are known to regulate cell adhesion, shape and functions. The α8 integrin chain is expressed in glomerular mesangial cells and in vascular smooth muscle cells. Mice deficient for α8 integrin have structural alterations in glomeruli but not in renal arteries. For this reason we hypothesized that mesangial cells and vascular smooth muscle cells differ in their respective capacity to compensate for the lack of α8 integrin.ResultsWild type and α8 inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 45 publications
(52 reference statements)
2
15
1
Order By: Relevance
“…Overexpression of the itga8 did not lead to increases in the expression of matrix components (except for fi bronectin in tubular epithelial cells), but more likely to a downregulation of several matrix molecules. Thus, our results do not argue for an unequivocal profi brotic effect of itga8 expression, neither in mesenchymal nor in epithelial cells, although data from previous experiments (Marek et al, 2010) suggested that the expression of the itga8 might promote a phenotypic change to a more activated mesenchymal phenotype, which is responsible for increased matrix production of cells affected.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Overexpression of the itga8 did not lead to increases in the expression of matrix components (except for fi bronectin in tubular epithelial cells), but more likely to a downregulation of several matrix molecules. Thus, our results do not argue for an unequivocal profi brotic effect of itga8 expression, neither in mesenchymal nor in epithelial cells, although data from previous experiments (Marek et al, 2010) suggested that the expression of the itga8 might promote a phenotypic change to a more activated mesenchymal phenotype, which is responsible for increased matrix production of cells affected.…”
Section: Discussioncontrasting
confidence: 88%
“…Profi brotic agents like TGF β -1 and angiotensin II are able to induce the expression of the itga8 in different cell types, supporting the notion that α 8 β 1 integrin might exert profi brotic effects (Bouzeghrane et al, 2004;Hartner et al, 1999). Mesangial cells defi cient for the itga8 downregulate the expression of α -smooth muscle actin (a marker of myofi broblast activation) and the profi brotic cytokine CTGF (Marek et al, 2010), further arguing for a contribution of α 8 β 1 90 G. VOLKERT ET AL.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…They are composed of integrin ␣ (Itg ␣) and integrin ␤ (Itg ␤) subunits, and each Itg ␣␤ combination has its own signaling properties and binding specificity. A number of integrin subunits, such as ␣v, ␣4, ␣5, ␣6, ␤1, ␤3, ␤4, ␤5, ␣6␤1, and ␣␤3, are expressed in SMCs (33)(34)(35). We found that the specific antibodies against ␣v, ␣6, ␤1, ␤3, ␣6␤1, and ␣␤3 significantly blocked PDGF-BBinduced SMC migration, but the antibodies against ␣4, ␣5, ␤4, and ␤5 had no effect on PDGF-BB-induced SMC migration (Fig.…”
Section: Pdgf-bb-induced Cyr61 Has No Feedback Effect On the Activatimentioning
confidence: 72%
“…Alpha8 integrin ( Itga8 ) is an RGD binding integrin which is expressed on mesangial cells and regulates their biological properties including adhesion, proliferation, migration and apoptosis by interacting with extracellular ligands such as fibronectin, vitronectin or osteopontin [22, 23]. Its role for phagocytosis is not yet known.…”
Section: Introductionmentioning
confidence: 99%